Knowledge Sharing and Organizational Performance: Case Study in Indonesia Service Company - Ine Madinatul Munawaroh; Rofiaty; Ainur Rofiq (Jurnal Mebis, 2024)
This study aims to explore the role of knowledge sharing at PT. Malika Goenawan Erawisata in achieving organizational performance. This study used qualitative approach by phenomenology design to describe the applied model of knowledge sharing including knowledge acquisition, knowledge dissemination, and responsiveness of the knowledge. The collecting data used in-depth interview to 13 informants such as the leaders, employees, and customers. The data analysis used the interactive model of miles and Huberman. This study found that the applied model of knowledge sharing in knowledge acquisition acquired from customers, employees, the tacid knowledge of company's leaders, and seminars. In addition, the knowledge sharing model in knowledge dissemination involved meetings, direct communication, and the use of information technology such as social media. Meanwhile, the responsiveness of the knowledge lead to make tasks easier to accomplished, especially in marketing strategy planning. Furthermore, the organizational performance well established. But, overall, the knowledge sharing was processed conventionally and the knowledge dissemination was not spread yet proportionally to the whole employees. Hence, it needs the creative and innovative program to motivate employees and increase organizational performance optimally.